PENGARUH VIRTUAL COORDINATOR TRAINING TERHADAP KOMPETENSI PEDAGOGIK DAN PROFESIONAL - Harsiana Wardani (STKIP Subang, 2022)
The aims of this study were to: (1) analyze the effect of Virtual Coordinator Training on teacher pedagogic competence in Indonesia, (2) analyze the effect of pedagogic competence on teacher professional competence in Indonesia, (3) analyze the effect of Virtual Coordinator Training on teacher professional competence in Indonesia, and (4) analyze the effect of Virtual Coordinator Training on professional competence through the pedagogic competence of teachers in Indonesia. This research is included in the quantitative research design. The population in this study were all teachers in Indonesia who took part in the Virtual Coordinator Training batch 5 and were declared to have passed as many as 725 teachers. The sampling technique used in this study is through Quota Random Sampling. In this study, the samples taken were elementary school teachers in Indonesia. Through this sampling technique, the number of research samples is 251 teachers, which has exceeded the minimum sample size. Data collection was carried out through distributing questionnaires. The data analysis technique used was SEM (Structured Equation Modeling) based on PLS (Partial Least Square) using SmartPLS 3.3.5 software. The results of this study indicate that: (1) Virtual Coordinator Training has an effect on the pedagogical competence of teachers in Indonesia. The influence of Virtual Coordinator Training on the pedagogical competence of teachers in Indonesia is a positive and significant influence. (2) Pedagogic competence influences the professional competence of teachers in Indonesia. The influence of pedagogic competence on the professional competence of teachers in Indonesia is a positive and significant influence. (3) Virtual Coordinator Training has no significant effect on the pedagogical competence of teachers in Indonesia. The effect of Virtual Coordinator Training is positive on the professional competence of teachers in Indonesia but this effect is not significant. (4) Virtual Coordinator Training has a positive and significant indirect effect on professional competence through the pedagogical competence of teachers in Indonesia. The indirect effect of Virtual Coordinator Training on teacher pedagogic and professional competence in Indonesia is a positive and significant influence.